Pengaruh Antara Pola Asuh Permisif Terhadap Kecerdasan Emosi Pada Siswa Kelas X SMK Negeri 9 Samarinda. - Wahyuni, Emy Nur (MOTIVASI, 2014)
This study aims to determine whether there is a significant influence of permissive parenting on emotional intelligence of students grade 9 SMKN Samarinda. In this study, the independent variable is permissive parenting, while the dependent variable is emotional intelligence. The hypothesis is